(untitled) (Praxis Educativa, 2025)
Sugar is a substance that has been positioned since colonial times based on a discourse that masks negative connotations, such as being portrayed by the mass media under the repeated lie that it is a food and a staple of the household diet. However, from the origins of its production and marketing process, it bears the objective complicity of capitalism in direct relation to the various violent forces that have emerged in the territory since that time, seeking to impose slavery in the Americas. Based on a qualitative, comprehensive, interpretive research study developed within the framework of a doctoral research project, this paper examines the thinking of authors such as Frantz Fanon, Mignolo, Foucault, and Quijano, among others. The objective is to link sugar as a device of power that, through discourse, naturalized racial violence and justified slave-based capitalism.